Dakwah Islam Multikultural Pada Komunitas Sunda, Arab Alawi dan Arab Irsyadi - Sukriadi Sambas; Indira Sabet Rahmawaty; Ratna Dewi (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2019)
The characteristics of Islam as a religion of da’wa makes Islam capable of crossing the walls of diversity in society, creating harmony, providing solutions to diversity and even conflict. This multicultural aspect can be seen in the meeting of the elements of da’wa: da'i, mad'u, messages and media of da’wa. The multiculturalist aspect is examined qualitatively descriptive in the process of dakwah in the Sundanese community, Alawi Arabs and Irsyadi Arabs. The Sundanese, Arab Alawi and Arab Irsyadi communities are qualified as competent da'i. Scientific competence is symbolized in the title carried by da'i. This title is one of the important factors in the image of da'i. The da'i title is Kyai, Ajengan and the teacher for the Sundanese community; Habib, Syarif and Sayid for the Arab Alawi community; and an academic degree for the Irsyadi Arab community. If all communities appreciate the differences shown by the respective communities. Mad'u from three communities mingled at the same time and place in certain da’wa events, and parted ways in a typical community events. Da’wa messages delivered by the three communities are the same and some are unique. But the source of the message is the same, namely Al-Quran and As-Sunnah. For the Irsyadi Arab community Ijma and qiyas were not added except for the Sundanese and Alawi Arabs. Wasilah (media) propaganda is the same except the Irsyadi Arab community does not use media in its opinion including bid'ah and khurafat. AbstrakKarakteristik Islam sebagai agama dakwah membuat Islam mampu melintasi dinding-dinding keragaman masyarakat, mewujudkan keharmonisan, memberi solusi atas keragaman bahkan konflik. Aspek multikultural ini terlihat dalam pertemuan unsur-unsur dakwah: da’i, mad’u, pesan dan wasilah dakwah. Aspek multikulturalis diteliti secara kualitatif deskriptif dalam proses dakwah di komunitas Sunda, Arab Alawi, dan Arab Irsyadi. Da’i komunitas Sunda, Arab Alawi, dan Arab Irsyadi memiliki kualifikasi sebagai da’i yang kompeten. Kompetensi keilmuan disimbolkan dalam gelar yang disandang da’i. Gelar ini menjadi salah satu faktor penting citra da’i. Gelar da’i yaitu Kyai, Ajengan dan pak guru bagi da’i komunitas Sunda; Habib, Syarif dan Sayid bagi da’i komunitas Arab Alawi; dan gelar akademik bagi da’i komunitas Arab Irsyadi. Da’i semua komunitas menghargai perbedaan yang ditunjukan uruf masing-masing komunitas. Mad’u dakwah dari tiga komunitas berbaur pada waktu dan tempat yang sama dalam event-event dakwah tertentu, dan berpisah dalam event dakwah khas perkomunitas. Pesan dakwah yang disampaikan da’i ketiga komunitas ada yang sama dan ada yang khas. Namun sumber pesannya sama, yaitu Al-Quran dan As-Sunah. Bagi komunitas Arab Irsyadi tidak ditambah ijma dan qiyas kecuali bagi komunitas Sunda dan Arab Alawi. Wasilah (media) dakwahpun sama kecuali komunitas Arab Irsyadi tidak menggunakan media yang dalam pendapatnya termasuk bid’ah dan khurafat.